A Test of Static Trade-Off Theory and Pecking Order Theory on Malaysia Firms' Growth Opportunities and Financial Decision Policy - Goh, Siew Ping (Universiti Malaysia Sarawak (UNIMAS), 2011)
Capital is defined as an important and critical resource for all companies in all countries and the capital can be divided into two categories which are equity and debt. When companies finance its operation and investing activities with the funds obtained from the selling of ownership rights and assets, it’s called equity financing. On the contrary, debt financing happened when companies borrow an amount of money from others and repay it together with the principle and interest within a stipulated time frame. There are many definitions has been given to capital structure of companies. From the definitions given by many previous researchers, capital structure can be defined as the mix of the diverse funds obtained by the firm. It is summarized that an appropriate and accurate capital structure is an important decision for any business organization to avoid the losses happens to shareholder and also at the same time to maximum the return and minimum the risk (Meyers, 1984; Fraser, Zhang, & Derashid, 2006; Bevan & Danbolt, 2002). In order to investigate how varying the firms’ growth opportunities and financial decision policy bring their implications on capital structure for companies at different countries, there are several theories have been built up. All the theories have evolved along many directions and it suggest that firms is depend on the features that influence the costs and benefits associated with debt and equity financing, by selecting a appropriate capital structure. There are four basic theories that explain the capital structure of the companies; Trade-off Theory, Pecking Order Theory, Agency Cost Theory and Signaling Theory.